The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1159/000098188
|View full text |Cite
|
Sign up to set email alerts
|

Class I genes have split from the MHC in the tammar wallaby

Abstract: Genes within the Major Histocompatibility Complex (MHC) are critical to the immune response and immunoregulation. Comparative studies have revealed that the MHC has undergone many changes throughout evolution yet in tetrapods the three different classes of MHC genes have maintained linkage, suggesting that there may be some functional advantage obtained by maintaining this clustering of MHC genes. Here we present data showing that class II and III genes, the antigen processing gene TAP2, and MHC framework gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 64 publications
1
41
0
Order By: Relevance
“…High-density filters from the tammar wallaby BAC library (Me_KBa; Arizona Genomics Institute, Tucson, AZ, USA) were screened with pools of radioactively labelled PCR probes or overgos as described in (Deakin et al 2007). Resulting positive BACs were further screened with individual probes using dot blots of either purified BAC DNA spotted onto Hybond N+ membrane (GE Healthcare UK Ltd, Little Chalfont, Buckinghamshire, UK) or from BAC cultures spotted on Hybond N+ filters placed on LB plates containing 12 2g/ml chloramphenicol and then grown overnight at 37-C.…”
Section: Library Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…High-density filters from the tammar wallaby BAC library (Me_KBa; Arizona Genomics Institute, Tucson, AZ, USA) were screened with pools of radioactively labelled PCR probes or overgos as described in (Deakin et al 2007). Resulting positive BACs were further screened with individual probes using dot blots of either purified BAC DNA spotted onto Hybond N+ membrane (GE Healthcare UK Ltd, Little Chalfont, Buckinghamshire, UK) or from BAC cultures spotted on Hybond N+ filters placed on LB plates containing 12 2g/ml chloramphenicol and then grown overnight at 37-C.…”
Section: Library Screeningmentioning
confidence: 99%
“…Although the virtual map will be a great aid to genome assembly, it is important to note that it can only act as a guide, as some genes may be missing from the opossum genome assembly that are present in the wallaby and vice versa, or there may be small-scale rear- rangements not detected by mapping just a few genes from these blocks. For example, MHC Class I genes have been assigned to three different locations on wallaby chromosome 5 (Deakin et al 2007) but no orthologues of these genes are found on opossum chromosome 4.…”
mentioning
confidence: 99%
“…Specificity of the overgo probes was checked by searching the elephant trace archive using BLASTN. Selected overgos were radioactively labeled with 32 P-dATP and 32 P-dCTP and hybridized to male elephant BAC library (VMRC-15) filters (BAC PAC Resources, CHORI) in pools of ten according to methods described in Deakin et al (2007). After hybridization and washes, filters were exposed to X-ray film for 1 week at −80°C.…”
Section: Bac Library Screeningmentioning
confidence: 99%
“…Using pools of radioactively labelled overgos, the tammar wallaby BAC library (Me_KBa; Arizona Genomics Institute, Tucson, Ariz., USA) was screened following the protocols described in Deakin et al [2007]. Positive BACs were confirmed to contain the gene of interest by screening dot blots of BAC cultures with a single pair of overgo probes as described in Deakin et al [2008].…”
Section: Tammar Wallaby Bac Library Screeningmentioning
confidence: 99%